Study on Effective Ways to Control Blood Sugar: Understanding the Impact of Fasting on the Health of Diabetics (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Diabetes is one of the fastest increasing metabolic diseases in the world today. Lifestyle changes have led to increased level of diabetes across all age groups. Initially, diabetes was known as sweet urine because in a chronic state of the disease, glucose is passed to the urine. The main objective of this paper is to evaluate the effect of irregular food intake (fasting) on the health of diabetics. The topic about the effect of fasting on the health of diabetics especially during Ramadan touches a real situation that should be addressed appropriately. Diabetes is a disease that has killed many people and provision of information about its effects is an essential way of ensuring that people know more about the disease. Fasting is an essential element of strengthening the faith of Islam and Muslims need to have adequate information about their health especially in the case of diabetics. In order to comprehensively address this issue, it is important to understand the meaning of diabetes, the pathology, symptoms, and control of diabetes. In this paper we study about the impact of fasting on the Health of Diabetics.